2010
DOI: 10.1021/la1011132
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Spherical Vesicles in Electric Fields

Abstract: The stability of spherical vesicles in alternating (ac) electric fields is studied theoretically for asymmetric conductivity conditions across their membranes. The vesicle deformation is obtained from a balance between the curvature elastic energies and the work done by the Maxwell stresses. The present theory describes and clarifies the mechanisms for the four types of morphological transitions observed experimentally on vesicles exposed to ac fields in the frequency range from 500 to 2 × 107 Hz. The displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 42 publications
(106 reference statements)
1
53
0
Order By: Relevance
“…e l s e v i e r . c o m / l o c a t e / c i s and were able to solve experimental contradictions [20]. In particular, accounting for possible differences in solvent conductances inside and outside of the vesicle allows to obtain deformation from a spherical to an oblate vesicle under high AC fields [18,20].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…e l s e v i e r . c o m / l o c a t e / c i s and were able to solve experimental contradictions [20]. In particular, accounting for possible differences in solvent conductances inside and outside of the vesicle allows to obtain deformation from a spherical to an oblate vesicle under high AC fields [18,20].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…This tubelike shape is an equilibrium structure given by the bending energy and the external forces and allows subsequently for an estimate of the bending energy [11]. Further experiments revealed that this particular sequence of action depends very much on the actual mechanical properties [12][13][14][15][16][17][18][19][20][21][22][23]. Lengthy calculations accounting for the detailed electric field distribution revealed only minor corrections [12].…”
Section: Introductionmentioning
confidence: 99%
“…This polarizability depended on the field strength but was shown to decrease with an ionic strength increase in the same way as the double electric layer thickness did. It was reported indeed that the electric polarizability increased linearly with the increase in the minus half power of KCl concentration [12,13]. We might expect a high polarizability in the 3 μS/cm solution meaning a faster reorientation than under the other conductivity conditions.…”
Section: Discussionmentioning
confidence: 77%
“…Electrofusion-based reactions in GUVs strongly rely on the physical behavior (deformation, poration and fusion) of these vesicles subjected to either alternating current field or strong direct current (DC) pulses. In recent years, our group has systematically investigated this topic by experimental and theoretical modeling (Riske et al, 2005;Riske et al, 2006;Haluska et al, 2006;Dimova et al, 2007;Aranda et al, 2008;Riske et al, 2009;Vlahovska et al, 2009;Dimova et al, 2009;Yamamoto et al, 2010). Based on the findings from our and other research groups, successful electrofusion is b a s e d o n f o u r i m p o r t a n t f e a t u r e s o f t h e membrane and the vesicles: 1) The lipid membrane is impermeable to reactants (ions and macromolecules), while water can freely permeate through the membrane to assure osmotic balance; 2) Fast and effective fusion could be initiated with a short electric pulse with characteristics above the poration threshold of the membrane; 3) Leakage of reactants during the fusion process is negligible (Riske et al, 2005); 4) Vesicles with complementary reactants can be brought together to form a reactive couple for electrofusion.…”
Section: Wwwintechopencommentioning
confidence: 99%